The effects of acid aspiration on tissue-resident macrophages in extra-pulmonary organs - Langelage, Martin; Justus Liebig University Giessen (My University, 2024)
Acid aspiration is a major cause of ALI and induces sterile pneumonitis. The immune response to acid aspiration is not limited to the lungs but also involves extrapulmonary organs. This study investigated the effects of acid-induced ALI on TRMs in the kidneys, the liver, the peritoneum, and the spleen at indicated time points after aspiration in a mouse model. Kidney TRMs displayed a pro-inflammatory phenotype with upregulation of IL-1ß and IL-6 transcripts 24h after aspiration. Flow cytometric analysis revealed an increased IL-6 protein synthesis at this time. Creatinine levels were unaltered one day after aspiration but mounted eight days afterward. Subsequent histopathologic analysis did not show any tissue damage. Further transcriptional analysis revealed key metabolic enzymes, especially the TCA cycle regulator enzyme IDH-1, to be distinctly downregulated 24h after acid aspiration in hepatic, splenic, and peritoneal TRMs with the most marked manifestation in liver TRMs. Ex vivo seahorse analysis of liver TRMs unveiled a distinct impairment to perform OXPHOS one day after aspiration. Bacterial killing assays performed ex vivo with P. aeruginosa and K. pneumoniae revealed a marked impairment in the bactericidal activity of liver TRMs 24h after aspiration, while splenic and peritoneal TRMs were not affected. The following investigation unraveled a compromised generation of mROS upon bacterial encounter as a mechanism for the impairment in bactericidal activity. Subsequent analysis did not detect hepatic inflammation as an elicitor of the alterations in liver TRMs. The liver harbors the majority of macrophages in a mammal's body and is crucial for clearing bacteria from systemic circulation. We found liver TRMs to be involved in the systemic response to acid aspiration. Their impaired bactericidal activity one day after aspiration may thus result in increased susceptibility to nosocomial infection after aspiration as commonly seen in intubated patients.
Keywords: Aspiration; Leber; Niere; Milz; Peritoneum; Immunologie; ddc:500; ddc:610